PROMOTING CHILDREN’S CONSERVATION AWARENESS OF Macaca fascicularis THROUGH NARRATIVE VIDEO - Anggraini, Fatimah Dwi; Budi Prasetyo, Andreas Priyono; Iswari, Retno Sri (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
This research and development (R&D) aimed to develop a narrated video of monkey’s daily behavior Macaca fascicularis for conservation education. This R&D were conducted by the following steps as identification of potentials and problems of creating the video, data collection, video design, validation by media and content experts, revisions, and the limited field-testing of final products. To collect data some research instruments were developed such as validation sheets, feasibility test, and attitude scales. The data were analysed descriptively and quantitatively. The results showed that scores of validation video were classified as’valid’ (94, 23% and 87,5%). Video media was also rated ‘feasible’ (95,24%) by the local forest tourism manager. Level of children conservation awareness is ‘high’ (88, 42%). In sum, the videos are valid, feasible, and effective in instilling conservation awareness as well ready for use in promoting children’s awreness of long-tail monkey Macaca fascicularis protection.